COMPATIBILITY OF INDONESIA'S REGULATIONS ON SUBMARINE CABLE WITH UNCLOS 1982 - Agustina Merdekawati; Swissitya Ajari; Irkham Afnan Trisandi Hasibuan; I Gusti Putu Agung (Arena Hukum, 2021)
AbstractThe special status of Exclusive Economic Zone of Indonesia (EEZ) raises a problem particularly related to the submarine cable laying activities. This study aims to analyze the compatibility of the marine location permit instrument under Law No. 32/2014 on Marine Affairs and Government Regulation No. 32/2019 on National Marine Spatial Planning (MSP) with UNCLOS 1982 in regulating submarine cable in the EEZ. This normative research shows that the marine location permit instrument regulating submarine cable laying activity in EEZ is incompatible with the provisions of UNCLOS 1982. In contrast, the MSP instrument is compatible and a suitable instrument to protect Indonesia's interests in the EEZ. The Government of Indonesia is advised to regulate an exemption clause for submarine cable installation in EEZ in the Draft of Government Regulation on Marine Location Permit; formulate and formalize ‘prior notification’ procedures by other countries in submarine cable laying activities in EEZ into laws and regulations; and publish the Government Regulation on Marine Spatial Planning and its annexes through the channels of relevant international organizations such as International Cable Protection Committee (ICPC) and Intergovernmental Oceanographic Commission (IOC).AbstrakKekhususan Zona Ekonomi Eksklusif Indonesia (ZEE) menimbulkan permasalahan terkait bentuk instrumen hukum yang dapat diterapkan oleh Indonesia untuk mengatur aktivitas pemasangan kabel bawah laut. Penelitian ini bertujuan untuk menganalisis kesesuaian instrumen izin lokasi laut dalam Undang-Undang 32/2014 tentang Kelautan; dan Peraturan Pemerintah 32/2019 tentang Rencana Tata Ruang Laut (PP RTRL) terhadap UNCLOS 1982 dalam mengatur aktivitas pemasangan kabel bawah laut di ZEE. Hasil penelitian normative ini menunjukkan bahwa instrumen izin lokasi laut tidak berkesesuaian dengan ketentuan UNCLOS. Sementara, instrumen rencana tata ruang laut berkesesuaian dengan ketentuan UNCLOS sehingga menjadi instrumen yang tepat untuk melindungi kepentingan Indonesia. Tim peneliti merekomendasikan kepada Pemerintah Indonesia untuk mengatur klausul pengecualian terhadap pemasangan kabel bawah laut di ZEE dalam Rancangan PP Izin Lokasi Laut; memformulasikan dan merumuskan prosedur ‘prior notification’ oleh negara lain dalam aktivitas pemasangan kabel bawah laut di ZEE ke dalam peraturan perundang-undangan, dan memublikasikan eksistensi PP RTRL beserta lampiran-lampirannya melalui kanal organisasi-organisasi internasional terkait seperti International Cable Protection Committee (ICPC) dan Intergovernmental Oceanographic Commission (IOC).